Modern public economics - Jha, Raghbendra (Routledge advanced texts in economics and finance., 2010)
The new edition of Jha's€popular text comes with a supporting website and builds on the strength of the previous edition by increasing the international coverage including global public goods and highlighting the issue of environmental taxation. €.